Recent advances in the rational design of 2D MXenes in energy conversion and storage systems. (23rd June 2021) - Sheikh, Nayab; Tahir, Muhammad Bilal; Fatima, Nisar; Sagir, Muhammad; Pervaiz, Muhammad; Tahir, M. Suleman
Summary: The most encouraging prospect of energy storage gadgets is batteries and supercapacitors to overcome the need for energy. The environmental problems presently captivate a huge interest in scientific awareness. The improvement of two‐dimensional (2D) profoundly effective cathode materials is the way to new research in the fields of energy transformation as well as energy storage devices. MXenes, another fascinating group of 2D transition metal carbides, nitrides and carbo‐nitrides has gained impressive consideration because of their phenomenal properties like high electrical conductivity, hydrophilic nature, magnificent thermal strength, huge interlayer separation, effectively tunable construction, and high surface area. In this review, various MXenes synthesis courses utilizing distinctive materials for example hydrofluoric acid, ammonium hydrazine, lithium fluoride, and hydrochloric acid have been discussed. Additionally, different combinations of MXenes with the leading polymers are still there and should have been investigated. Potential applications of MXenes have also been discussed in the perspective of energy harvesting. MXenes have been proved as promising candidates to resolve the energy crisis because of their pre‐eminent applications in batteries, supercapacitors, and cells. MXenes have also been used for carbon dioxide reduction and hydrogen production. Abstract : Current work explains the fundamental structure, synthesis, and novel applications of MXenes in the provision and conversion of energy. Previous work on MXenes has not provided a contrast between MXenes and other materials being used in energy applications however current work focuses on that.